Preparation process of catalyst for treating carbon-containing tail gas
Through the doping modification of graphyne and graphene and the preparation of composite hydrogel, combined with the roasting treatment of ferromanganite and nickel nitrate, the problems of insufficient catalyst stability and catalytic efficiency in the existing technology have been solved, and the efficient removal of carbon dioxide has been achieved. The effect of harmful substances in carbon exhaust.
Patent Information
- Application Number
- CN202410996937.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-24
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-07-24
AI Technical Summary
The prior art is difficult to effectively remove harmful substances in carbon-containing exhaust gas, and the stability and catalytic efficiency of the catalyst are insufficient, which affects the efficiency and effect of exhaust gas treatment.
A composite catalyst was prepared by using a mixture of graphyne and graphene for doping modification, combined with the composite hydrogel of sodium tetraborate, ferromanganite and nickel nitrate and roasting treatment. This method uses hydrothermal reaction and multiple roasting steps to form a catalyst with high conductivity, stability and active sites.
The catalytic efficiency and stability of the catalyst are improved, and harmful substances in carbon-containing exhaust gas can be efficiently removed at lower temperatures and in a shorter time, with a conversion rate of more than 99.3%.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts and relates to a preparation process of a catalyst for treating carbon-containing tail gas. Background Art
[0002] Carbon monoxide and other harmful substances in carbon-containing exhaust gas can have a serious impact on air quality. These substances accumulate in the atmosphere, forming smog and harmful gases, which have a negative impact on human health, such as respiratory diseases, cardiovascular diseases, etc.
[0003] At present, most methods for treating carbon-containing tail gas are to convert CO and HC in the tail gas into harmless gases or substances that are easy to handle through the action of catalysts. At the same time, the catalyst itself has high stability and anti-toxicity, and will not cause harm to the human body and the environment. By introducing a catalyst, the chemical reaction rate can be accelerated, thereby efficiently removing harmful substances in the exhaust gas. Catalytic combustion exhaust gas treatment equipment can effectively remove harmful substances in the exhaust gas, and its removal rate can reach more than 90%. Therefore, the performance of the catalyst directly affects the efficiency and effect of exhaust gas treatment. With the continuous improvement of environmental protection requirements, the performance of exhaust gas treatment catalysts has also been continuously improved, the catalytic system has become more complex, and the catalyst's pertinence, selectivity and catalytic efficiency have continued to improve. Therefore, the present invention provides a preparation process for a catalyst for treating carbon-containing tail gas, and the catalyst prepared by the method has high catalytic efficiency and good stability. Summary of the invention
[0004] The object of the present invention is to provide a process for preparing a catalyst for treating carbon-containing tail gas, which has the characteristics of high catalytic efficiency and high stability.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A preparation process of a catalyst for treating carbon-containing tail gas, the specific preparation process of the catalyst is as follows:
[0007] S1: Gdyne and graphene are mixed in a mass ratio of 1:10, and ground in a ball mill at a speed of 300 r / min to obtain a nano-mixture A with a particle size of 200 mesh;
[0008] S2: Disperse the nanomixture A in deionized water and ultrasonicate at 25°C for 0.5 h to obtain a mixed solution B with a concentration of 5-10 mg / ml;
[0009] S3: Sodium tetraborate with a concentration of 30-50 mg / ml and mixed solution B were fully mixed at a volume ratio of 1:50, and ultrasonicated at 25°C for 0.5 h to obtain mixed solution C;
[0010] S4: Under a nitrogen atmosphere, the mixed solution C was subjected to a hydrothermal reaction, the temperature was slowly raised from room temperature to 100°C for the first time, and after reacting at 100°C for 2 hours, the temperature was raised to 180°C for the second time, and after reacting for 6 hours, a composite hydrogel D was obtained;
[0011] S5: The composite hydrogel D was immersed in a hydroalcohol solution for 1 hour, and then placed in liquid nitrogen for freezing for 10 minutes. After being completely frozen, it was dried in a freeze dryer at -30°C for 4 hours to obtain a freeze-dried mixture E;
[0012] S6: putting the iron manganese ore and nickel nitrate into a ball mill and grinding them at a speed of 500 r / min, wherein the mass ratio of the iron manganese ore to the nickel nitrate is 3:1, to obtain a crushed mixture, repeatedly washing the crushed mixture with deionized water, and drying the washed mixture at 60° C. to obtain a dry solid powder F;
[0013] S7: using boric acid with a concentration of 5% to pickle the solid powder F at 25°C. After pickling, nitrogen is uniformly sprayed onto the powder surface at 120°C to dry the powder, thereby obtaining a dry solid powder G.
[0014] S8: calcining the solid powder G for the first time under a nitrogen atmosphere at a temperature of 500° C. for 3 h to obtain a dry solid powder H;
[0015] S9: Mix the mixture E and the solid powder H in a mass ratio of 2:3, add 1 wt % of polyethylene glycol, and grind in a ball mill at a speed of 300 r / min under a nitrogen atmosphere for 0.5 h to obtain a mixed powder I;
[0016] S10: The mixed powder I is heated to 300° C. at a rate of 2° C. / min under a nitrogen atmosphere, and is calcined for a second time at 300° C. for 4 h. After the calcination is completed, the temperature is slowly cooled to room temperature and ground to obtain the catalyst.
[0017] Furthermore, the first slow heating rate in S4 is 2°C / min.
[0018] Furthermore, the second heating rate in S4 is 5°C / min.
[0019] Furthermore, the volume ratio of the water-alcohol solution in S5 is ethanol: water, which is 1:5.
[0020] Furthermore, the flow rate of nitrogen injection in S7 is 2.5m 3 / min, the pressure is 3MPa.
[0021] Furthermore, the molecular weight of the polyethylene glycol in the S9 is 2000-4000.
[0022] Furthermore, the slow cooling rate in S10 is 2° C. / min.
[0023] Furthermore, the catalyst particles obtained by grinding in S10 have a particle size of 200 meshes.
[0024] The catalyst used in the present invention is a composite catalyst, which is composed of a metal catalyst and a non-metal catalyst. The metal catalyst usually has excellent adsorption and activation capabilities, while the non-metal catalyst may have a unique catalytic mechanism. When the two are combined, they can produce a synergistic effect and accelerate the reaction rate. Therefore, compared with a single catalyst, it has higher catalytic efficiency and better stability.
[0025] As allotropes of carbon, graphyne and graphene have abundant carbon sources and diverse structures. Their mixture can prepare a non-metal catalyst with complex structure and multiple active sites. Both graphene and graphyne have excellent conductivity and stability. The non-metal catalyst prepared by mixing the two makes the catalyst have better electron transmission ability and stability during the reaction process. In order to better improve the performance of the catalyst, the present invention uses boron and nitrogen elements to dope and modify the mixture of graphyne and graphene. The doping of boron and nitrogen can change the electronic structure of graphene and graphyne, thereby introducing new active sites on the catalyst surface. These active sites can reduce the activation energy of the carbon removal reaction, improve the catalytic activity of the catalyst, and enable the carbon removal reaction to proceed at a lower temperature or in a shorter time; boron and nitrogen doping can enhance the structural stability of graphene and graphyne, and reduce the structural damage of the catalyst under high temperature or high chemical activity environment. This improvement in stability helps to increase the service life of the catalyst and reduce maintenance costs; in addition, the d orbital of the boron atom can form a specific chemical bond with the π orbital of graphene and graphyne, thereby breaking the symmetry of graphene and graphyne and improving the electrical conductivity. The increase in conductivity can promote the transmission and transfer of electrons on the catalyst surface, which helps to accelerate the electron transfer process in the carbon removal reaction and improve the catalytic efficiency.
[0026] In the present invention, graphyne and graphene are mixed in a mass ratio of 1:10. In the hydrothermal reaction, sodium tetraborate reacts with the functional groups on the surface of graphene and graphyne to form chemical bonds or physical crosslinks, thereby constructing a three-dimensional network structure. At the same time, water molecules are also adsorbed into the network structure to form a composite hydrogel. At this ratio, the composite hydrogel prepared by mixing graphene, graphyne and sodium tetraborate in a nitrogen atmosphere has good conductivity, flexibility and mechanical strength. If the ratio of graphyne is too high, the conductivity of the composite hydrogel obtained will decrease. In addition, during the hydrothermal reaction, the present invention first reacts at 100°C. At this temperature, the morphology and particle size of the reactants can be better controlled, so that the catalyst has more active sites. After the reaction is stable, the temperature is raised to 180°C to increase the reaction rate.
[0027] In the present invention, a mixture of ferromanganese ore and nickel nitrate is selected as a metal catalyst, the mixture of ferromanganese ore and nickel nitrate is crushed and washed to remove surface impurities, and then nitrogen is purged to improve its stability, further reduce impurities generated by oxidation, and maintain a stable temperature in the reaction system.
[0028] The present invention selects ferromanganese ore as a main component. The ferromanganese ore is a mineral resource widely existing in nature. Compared with the iron-manganese compound prepared by compounding, it does not need to go through a multi-step chemical reaction and a purification process, thereby reducing the production cost; the iron and manganese elements in the ferromanganese ore have formed a specific crystal structure and surface morphology in nature, and these structures often contain many natural active sites, and have better catalytic activity than the iron-manganese compound prepared by chemical means; the iron and manganese elements in the ferromanganese ore are closely symbiotic in nature, forming a unique synergistic effect, and this synergistic effect may make the ferromanganese ore show higher activity and selectivity in the catalytic reaction; in addition, the ferromanganese ore can be regenerated after the reaction as a catalyst to restore its catalytic activity, and this renewability not only reduces the use cost of the catalyst, but also helps to reduce the generation of waste and environmental pollution.
[0029] The present invention firstly performs a first roasting of a mixture of ferromanganese ore and nickel nitrate at 500°C in a nitrogen atmosphere. During the roasting process of the ferromanganese ore at 500°C, the crystal water and part of the volatile substances inside the ferromanganese ore are removed, thereby improving the structure and properties of the mineral, which is conducive to the mixing and reaction of the ferromanganese ore with graphyne and graphene in the subsequent treatment process. In the first roasting, the ferromanganese ore and the nickel nitrate react chemically, and the two are compounded to form a composite metal oxide. The addition of the nickel element enhances the interaction between the iron and manganese elements, promotes the electron transfer and charge distribution between them, thereby improving the catalytic activity and selectivity of the catalyst. This synergistic effect enables the composite metal oxide catalyst to show a better catalytic effect when treating carbon-containing tail gas. The composite structure of the composite metal oxide not only improves the thermal stability and chemical stability of the catalyst, but also helps to optimize the crystal structure and surface active site distribution of the catalyst. The addition of the nickel element promotes the formation of the composite structure, thereby improving the overall catalytic performance of the catalyst; in addition, the metal elements in the mixture participate in the redox cycle through the change of the metal valence state, and this redox cycle helps to release the accepting oxygen atoms, thereby improving the catalytic efficiency of the catalyst.
[0030] After the first roasting, the active sites on the surface and inside of the mixture of ferromanganese ore and nickel nitrate will increase, which is also conducive to a more complete reaction with graphyne and graphene during the second roasting process. In addition, high-temperature roasting can also destroy some of the crystal structures in the minerals, forming an intermediate state that is more prone to reaction; mixing graphyne and graphene with the roasted mixture of ferromanganese ore and nickel nitrate and roasting them again at 300°C can promote the interaction and bonding between them. Such a treatment process may make the mixture form a more stable structure, improve its electrical conductivity, thermal conductivity and mechanical strength; the temperature of the second roasting is relatively low (300°C), which also helps to reduce energy consumption and reduce the impact on the environment. At this temperature, polyethylene glycol (molecular weight 2000~4000) has also been completely decomposed. The addition of polyethylene glycol can reduce the catalyst particle size and roast evenly, so that there are more active sites. After such a treatment process, the final product has better performance. In addition, the two calcinations of the present invention are both carried out in a nitrogen atmosphere, which ensures the chemical stability during the calcination process and avoids the performance loss caused by oxidation. The mixing effect between the ferromanganese ore and the nickel nitrate mixture, and the graphyne and graphene will be better, and the substances can be mixed more evenly to form a more stable composite catalyst.
[0031] Beneficial effects of the present invention:
[0032] The present invention uses boron and nitrogen elements to dope and modify the mixture of graphyne and graphene. The doping of boron and nitrogen can change the electronic structure of graphene and graphyne, thereby introducing new active sites on the catalyst surface and improving the catalytic activity of the catalyst. The d orbital of the boron atom can also form a specific chemical bond with the π orbital of graphene and graphyne, thereby breaking the symmetry of graphene and graphyne and improving the electrical conductivity. The improvement of electrical conductivity can promote the transmission and transfer of electrons on the catalyst surface, which helps to accelerate the electron transfer process in the carbon removal reaction and improve the catalytic efficiency.
[0033] The present invention first performs a primary calcination of the iron manganese ore and nickel nitrate mixture at 500°C in a nitrogen atmosphere, and then performs a secondary calcination at 400°C with boron and nitrogen doped modified graphyne and graphene, so that a more stable composite catalyst can be formed between the four. DETAILED DESCRIPTION
[0034] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0035] Example 1
[0036] S1: Gdyne and graphene are mixed in a mass ratio of 1:10, and ground in a ball mill at a speed of 300 r / min to obtain a nano-mixture A with a particle size of 200 mesh;
[0037] S2: The nanomixture A was dispersed in deionized water and ultrasonicated at 25°C for 0.5 h to prepare a mixed solution B with a concentration of 5 mg / ml;
[0038] S3: Sodium tetraborate with a concentration of 30 mg / ml and mixed solution B were fully mixed at a volume ratio of 1:50, and ultrasonicated at 25°C for 0.5 h to obtain a mixed solution C;
[0039] S4: Under a nitrogen atmosphere, the mixed solution C was subjected to a hydrothermal reaction, the temperature was slowly raised from room temperature to 100°C at a rate of 2°C / min for the first time, and after reacting at 100°C for 2 hours, the temperature was raised to 180°C at a rate of 5°C / min for the second time, and after reacting for 6 hours, a composite hydrogel D was obtained;
[0040] S5: soaking the composite hydrogel D in a hydroalcohol solution for 1 hour, wherein the volume ratio of ethanol to water is 1:5, and then freezing it in liquid nitrogen for 10 minutes. After being completely frozen, drying it in a freeze dryer at -30°C for 4 hours to obtain a freeze-dried mixture E;
[0041] S6: putting the iron manganese ore and nickel nitrate into a ball mill and grinding them at a speed of 500 r / min, wherein the mass ratio of the iron manganese ore to the nickel nitrate is 3:1, to obtain a crushed mixture, repeatedly washing the crushed mixture with deionized water, and drying the washed mixture at 60° C. to obtain a dry solid powder F;
[0042] S7: Use 5% boric acid to pickle the solid powder F at 25°C. After pickling, use nitrogen to spray evenly onto the powder surface at 120°C for drying. The nitrogen spray flow rate is 2.5m 3 / min, the pressure is 3MPa, and a dry solid powder G is obtained;
[0043] S8: calcining the solid powder G for the first time under a nitrogen atmosphere at a temperature of 500° C. for 3 h to obtain a dry solid powder H;
[0044] S9: Mix the mixture E and the solid powder H in a mass ratio of 2:3, add 1 wt % of polyethylene glycol-2000, and grind them in a ball mill at a speed of 300 r / min under a nitrogen atmosphere for 0.5 h to obtain a mixed powder I;
[0045] S10: The mixed powder I is heated to 400° C. at a rate of 2° C. / min under a nitrogen atmosphere, and is calcined for a second time at 400° C. for 4 h. After the calcination, the temperature is slowly lowered to room temperature at a rate of 2° C. / min, and ground to obtain the catalyst. The catalyst particle size obtained by grinding is 200 mesh.
[0046] The catalyst prepared in this example has a conversion rate of 99.3% for carbon-containing tail gas.
[0047] Example 2
[0048] S1: Gdyne and graphene are mixed in a mass ratio of 1:10, and ground in a ball mill at a speed of 300 r / min to obtain a nano-mixture A with a particle size of 200 mesh;
[0049] S2: The nanomixture A was dispersed in deionized water and ultrasonicated at 25°C for 0.5 h to prepare a mixed solution B with a concentration of 10 mg / ml;
[0050] S3: Sodium tetraborate with a concentration of 30 mg / ml and mixed solution B were fully mixed at a volume ratio of 1:50, and ultrasonicated at 25°C for 0.5 h to obtain a mixed solution C;
[0051] S4: Under a nitrogen atmosphere, the mixed solution C was subjected to a hydrothermal reaction, the temperature was slowly raised from room temperature to 100°C at a rate of 2°C / min for the first time, and after reacting at 100°C for 2 hours, the temperature was raised to 180°C at a rate of 5°C / min for the second time, and after reacting for 6 hours, a composite hydrogel D was obtained;
[0052] S5: The composite hydrogel D is immersed in a hydroalcohol solution for 1 hour, wherein the volume ratio of ethanol to water is 1:5, and then placed in liquid nitrogen for freezing for 10 minutes. After being completely frozen, it is dried in a freeze dryer at -30°C for 4 hours to obtain a freeze-dried mixture E;
[0053] S6: putting the iron manganese ore and nickel nitrate into a ball mill and grinding them at a speed of 500 r / min, wherein the mass ratio of the iron manganese ore to the nickel nitrate is 3:1, to obtain a crushed mixture, repeatedly washing the crushed mixture with deionized water, and drying the washed mixture at 60° C. to obtain a dry solid powder F;
[0054] S7: Use 5% boric acid to pickle the solid powder F at 25°C. After pickling, use nitrogen to spray evenly onto the powder surface at 120°C for drying. The nitrogen spray flow rate is 2.5m 3 / min, the pressure is 3MPa, and a dry solid powder G is obtained;
[0055] S8: calcining the solid powder G for the first time under a nitrogen atmosphere at a temperature of 500° C. for 3 h to obtain a dry solid powder H;
[0056] S9: Mix the mixture E and the solid powder H in a mass ratio of 2:3, add 1 wt % of polyethylene glycol-4000, and grind them in a ball mill at a speed of 300 r / min under a nitrogen atmosphere for 0.5 h to obtain a mixed powder I;
[0057] S10: The mixed powder I is heated to 400° C. at a rate of 2° C. / min under a nitrogen atmosphere, and is calcined for a second time at 400° C. for 4 h. After the calcination, the temperature is slowly lowered to room temperature at a rate of 2° C. / min, and ground to obtain the catalyst. The catalyst particle size obtained by grinding is 200 mesh.
[0058] The conversion rate of the catalyst prepared in this example to carbon-containing tail gas is 99.3%.
[0059] Example 3
[0060] S1: Gdyne and graphene are mixed in a mass ratio of 1:10, and ground in a ball mill at a speed of 300 r / min to obtain a nano-mixture A with a particle size of 200 mesh;
[0061] S2: The nanomixture A was dispersed in deionized water and ultrasonicated at 25°C for 0.5 h to prepare a mixed solution B with a concentration of 10 mg / ml;
[0062] S3: Sodium tetraborate with a concentration of 50 mg / ml and mixed solution B were fully mixed at a volume ratio of 1:50, and ultrasonicated at 25°C for 0.5 h to obtain a mixed solution C;
[0063] S4: Under a nitrogen atmosphere, the mixed solution C was subjected to a hydrothermal reaction, the temperature was slowly raised from room temperature to 100°C at a rate of 2°C / min for the first time, and after reacting at 100°C for 2 hours, the temperature was raised to 180°C at a rate of 5°C / min for the second time, and after reacting for 6 hours, a composite hydrogel D was obtained;
[0064] S5: The composite hydrogel D is immersed in a hydroalcohol solution for 1 hour, wherein the volume ratio of ethanol to water is 1:5, and then placed in liquid nitrogen for freezing for 10 minutes. After being completely frozen, it is dried in a freeze dryer at -30°C for 4 hours to obtain a freeze-dried mixture E;
[0065] S6: putting the iron manganese ore and nickel nitrate into a ball mill and grinding them at a speed of 500 r / min, wherein the mass ratio of the iron manganese ore to the nickel nitrate is 3:1, to obtain a crushed mixture, repeatedly washing the crushed mixture with deionized water, and drying the washed mixture at 60° C. to obtain a dry solid powder F;
[0066] S7: Use 5% boric acid to pickle the solid powder F at 25°C. After pickling, use nitrogen to spray evenly onto the powder surface at 120°C for drying. The nitrogen spray flow rate is 2.5m 3 / min, the pressure is 3MPa, and a dry solid powder G is obtained;
[0067] S8: calcining the solid powder G for the first time under a nitrogen atmosphere at a temperature of 500° C. for 3 h to obtain a dry solid powder H;
[0068] S9: Mix the mixture E and the solid powder H in a mass ratio of 2:3, add 1 wt % of polyethylene glycol-2000, and grind them in a ball mill at a speed of 300 r / min under a nitrogen atmosphere for 0.5 h to obtain a mixed powder I;
[0069] S10: The mixed powder I is heated to 400° C. at a rate of 2° C. / min under a nitrogen atmosphere, and is calcined for a second time at 400° C. for 4 h. After the calcination, the temperature is slowly lowered to room temperature at a rate of 2° C. / min, and ground to obtain the catalyst. The catalyst particle size obtained by grinding is 200 mesh.
[0070] The conversion rate of the catalyst prepared in this example to carbon-containing tail gas is 99.9%.
[0071] Comparative Example 1
[0072] In this comparative example, no ferromanganese ore and nickel nitrate mixture is used in S6, and only ferromanganese ore is used. The remaining steps are consistent with those in Example 3.
[0073] The conversion rate of the catalyst prepared in this comparative example to carbon-containing tail gas is 97.5%.
[0074] Comparative Example 2
[0075] In this comparative example, the mixture of iron manganese ore and nickel nitrate is not used in S6, and only nickel nitrate is used. The remaining steps are consistent with those in Example 3.
[0076] The conversion rate of the catalyst prepared in this comparative example for carbon-containing tail gas is 96.3%.
[0077] Comparative Example 3
[0078] In this comparative example, the mixture of graphyne and graphene is not doped with boron and nitrogen elements for modification, and the remaining steps are consistent with those in Example 3.
[0079] The conversion rate of the catalyst prepared in this comparative example for carbon-containing tail gas is 95.8%.
[0080] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A process for preparing a catalyst for treating carbon-containing tail gas, characterized in that: The specific preparation process of the catalyst is as follows: S1: Gdyne and graphene are mixed in a mass ratio of 1:10, and ground in a ball mill at a speed of 300 r / min to obtain a nano-mixture A with a particle size of 200 mesh; S2: Disperse the nanomixture A in deionized water and ultrasonicate at 25°C for 0.5 h to obtain a mixed solution B with a concentration of 5-10 mg / ml; S3: Sodium tetraborate with a concentration of 30-50 mg / ml and mixed solution B were fully mixed at a volume ratio of 1:50, and ultrasonicated at 25°C for 0.5 h to obtain mixed solution C; S4: Under a nitrogen atmosphere, the mixed solution C was subjected to a hydrothermal reaction, the temperature was slowly raised from room temperature to 100°C for the first time, and after reacting at 100°C for 2 hours, the temperature was raised to 180°C for the second time, and after reacting for 6 hours, a composite hydrogel D was obtained; S5: The composite hydrogel D was immersed in a hydroalcohol solution for 1 hour, and then placed in liquid nitrogen for freezing for 10 minutes. After being completely frozen, it was dried in a freeze dryer at -30°C for 4 hours to obtain a freeze-dried mixture E; S6: putting the iron manganese ore and nickel nitrate into a ball mill and grinding them at a speed of 500 r / min, wherein the mass ratio of the iron manganese ore to the nickel nitrate is 3:1, to obtain a crushed mixture, repeatedly washing the crushed mixture with deionized water, and drying the washed mixture at 60° C. to obtain a dry solid powder F; S7: using boric acid with a concentration of 5% to pickle the solid powder F at 25°C. After pickling, nitrogen is uniformly sprayed onto the powder surface at 120°C to dry the powder, thereby obtaining a dry solid powder G. S8: calcining the solid powder G for the first time in an air atmosphere at a temperature of 500° C. for 3 h to obtain a dry solid powder H; S9: Mix the mixture E and the solid powder H in a mass ratio of 2:3, add 1 wt % of polyethylene glycol, and grind in a ball mill at a speed of 300 r / min under a nitrogen atmosphere for 0.5 h to obtain a mixed powder I; S10: The mixed powder I is heated to 300° C. at a rate of 2° C. / min under a nitrogen atmosphere, and is calcined for a second time at 300° C. for 4 h. After the calcination is completed, the temperature is slowly cooled to room temperature and ground to obtain the catalyst.
2. The process for preparing a catalyst for treating carbon-containing tail gas according to claim 1, characterized in that: The first slow heating rate in S4 is 2°C / min.
3. The process for preparing a catalyst for treating carbon-containing tail gas according to claim 1, characterized in that: The second heating rate in S4 is 5°C / min.
4. The process for preparing a catalyst for treating carbon-containing tail gas according to claim 1, characterized in that: The volume ratio of the water-alcohol solution in S5 is 1:5 for ethanol:water.
5. The process for preparing a catalyst for treating carbon-containing tail gas according to claim 1, characterized in that: The flow rate of nitrogen injection in S7 is 2.5m 3 / min, the pressure is 3MPa.
6. The process for preparing a catalyst for treating carbon-containing tail gas according to claim 1, characterized in that: The molecular weight of the polyethylene glycol in the S9 is 2000-4000.
7. The process for preparing a catalyst for treating carbon-containing tail gas according to claim 1, characterized in that: The slow cooling rate in S10 is 2°C / min.
8. The process for preparing a catalyst for treating carbon-containing tail gas according to claim 1, characterized in that: The catalyst particles obtained by grinding in S10 have a particle size of 200 meshes.
Citation Information
Patent Citations
Catalyst for purifying diesel engine tail gas NOX, CO and HC for vehicle and preparation method thereof
CN105688932A
Boron-nitrogen co-doped porous graphene as well as preparation method and application thereof
CN110540196A